EMS: An Energy Management Scheme for Green IoT Environments - Omar Said (IEEE Access, 2020)
The Internet of Things (IoT) has important applications in all aspects of our lives in areas such as business, military, security, and health. It is known that most IoT node designs are energy constrained. Therefore, maintaining an ideal energy consumption rate has become one of the most important challenges in the IoT research field. In this paper, an IoT Energy Management Scheme (EMS) is proposed. In this system, heterogeneous types of energy-constrained nodes are considered. The proposed EMS comprises three strategies. The first strategy minimizes the volume of data that may be transmitted through the IoT environment. The second strategy schedules the work of the critical energy IoT nodes. The third strategy provides a fault tolerance scenario that can be applied to address inevitable energy problems faced by IoT nodes. Finally, to test the proposed EMS, the NS2 network simulator is used to construct an intensive simulation of the IoT environment. The simulation results proved that the proposed EMS outperformed the traditional IoT system with respect to the following performance metrics: energy consumption rate, number of failed nodes due to energy loss, throughput, and network lifetime.